Improving healthcare through the use of 'medical manslaughter'? Facts, fears and the future. (September 2016) - Brazier, Margot; Devaney, Sarah; Griffiths, Danielle; Mullock, Alex; Quirk, Hannah
The criminal law looks set to play a larger role in regulating healthcare. Until recently, health professionals only faced the prospect of criminal liability if it could be proved that their gross negligence resulted in the death of a patient. In such a case, the professional could face a charge of gross negligence manslaughter (GNM). Prosecutions for 'medical manslaughter' have generated concern among doctors worried about what is perceived as a rise in the number of doctors facing criminal prosecution and the impact prosecutions are having on healthcare practice. May more frequent resort to the criminal process damage rather than promote better health care? In seeking to try to answer this question, the first problem is that reliable data in this area about how many prosecutions are brought and how they fare are limited due to the way cases are recorded. What evidence does exist is often based on media reports or samples that are not representative. This paper will argue that, while the real risk of being prosecuted for medical manslaughter remains low, such fears should not be dismissed because, as Donald Berwick has argued, 'fear is toxic' – for health professionals and their patients.